Taxpayer Compliance, Trust, and Power - Theresia Woro Damayanti; Samuel Martono (Jurnal Keuangan dan Perbankan, 2018)
Self-assessment system as adopted in Indonesia, focusing on taxpayer awareness. Therefore trust should be the spearhead of tax compliance rather than power. This study aims to examine how trust and power play a role in improving tax compliance by the slippery slope framework. Method of data collection in this research surveys in Central Java. The sampling technique is a multi-stage sampling that combines stratified random sampling and convenience sampling. Data has been collected from October 2015-April 2016, and 242 instruments were collected (86.4 percent response rate). By using multiple regression tests, the results of this study indicate that trust and power both simultaneously and partially affect tax compliance. Based on the coefficient different test, power has a greater impact than trust in creating tax compliance. This means that the compliance created in Indonesia is mandatory compliance that denies from self-assessment system that based on voluntary compliance.JEL Classification: H26; G41DOI: https://doi.org/10.26905/jkdp.v22i2.1580